Deletion of the tyrosine phosphatase Shp2 in cervical cancer cells promotes reprogramming of glutamine metabolism. Issue 4 (21st March 2023) - Gao, Xuehui; Kang, Jie; Li, Xiangke; Chen, Chuan; Luo, Duqiang
Abstract: Shp2 is a nonreceptor protein tyrosine phosphatase that is overexpressed in cervical cancer. However, the role of Shp2 in the regulation of cervical cancer metabolism and tumorigenesis is unclear. EGFR signaling pathways are commonly dysregulated in cervical cancer. We showed that Shp2 knockout in cervical cancer cells decreased EGFR expression and downregulated downstream RAS–ERK activation. Although AKT was activated in Shp2 knockout cells, inhibition of AKT activation could not make cells more sensitive to death. Shp2 depletion inhibited cervical cancer cell proliferation and reduced tumor growth in a xenograft mouse model. 1 H NMR spectroscopic analysis showed that glutamine, glutamate, succinate, creatine, glutathione, and UDP‐GlcNAc were significantly changed in Shp2 knockout cells. The intracellular glutamine level was higher in Shp2 knockout cells than in control cells. Further analysis demonstrated that Shp2 knockout promoted glutaminolysis and glutathione production by up‐regulating the glutamine metabolism‐related genes such as glutaminase (GLS). However, inhibition of GLS did not always make cells sensitive to death, which was dependent on glucose concentration. The level of oxidative phosphorylation was significantly increased, accompanied by an increased generation of reactive oxygen species in Shp2 knockout cells. Shp2 deficiency increased c‐Myc and c‐Jun expression, which may be related to the upregulation of glutamine metabolism. These findings suggested that Shp2 regulates cervical cancer proliferation, glutamine metabolism, and tumorigenicity. Abstract : Depletion of Shp2 improves glutamine metabolism by increasing glutamine uptake and reprogramming glutaminolysis. Shp2‐deletion cells activate AKT/GSK3 signal pathway and upregulate the expression of c‐Myc and c‐Jun, which may be involved in glutamine metabolism.